2018
DOI: 10.1016/j.dib.2018.04.147
|View full text |Cite
|
Sign up to set email alerts
|

Dataset on brand culture and perceived value of offerings to customers in the hospitality industry in Nigeria

Abstract: This study critically examines the role of brand culture in influencing the perceived value of offerings to customers within the hospitality industry in Nigeria. In today's competitive market, the extent at which organizations disregard the importance of developing a strong brand culture before communicating their value to the outside world has become worrisome. Hence, this study filled in the gaps and a total of 434 customers drawn from six different hotels in Lagos state, Nigeria, were sampled. The data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…In terms of brand value, Braunsberger and Munch ( 1998 ) showed that the consumer experience of brand value is acquired through various activities, existing in the stages of brand recognition, purchase decision-making, and product use. In terms of brand culture, the results of Dirisu et al ( 2018 ) showed that brand culture has a significant positive impact on the perceived experience value of the product. Quach et al ( 2020 ) believed that experience value has a positive impact on both brand attitude and purchase engagement.…”
Section: Theoretical Background Analysis and Research Hypothesesmentioning
confidence: 99%
“…In terms of brand value, Braunsberger and Munch ( 1998 ) showed that the consumer experience of brand value is acquired through various activities, existing in the stages of brand recognition, purchase decision-making, and product use. In terms of brand culture, the results of Dirisu et al ( 2018 ) showed that brand culture has a significant positive impact on the perceived experience value of the product. Quach et al ( 2020 ) believed that experience value has a positive impact on both brand attitude and purchase engagement.…”
Section: Theoretical Background Analysis and Research Hypothesesmentioning
confidence: 99%